Implementasi Program Makan Bergizi Gratis terhadap Perekonomian Keluarga Penerima Manfaat dalam Perspektif Maqasid Al-Syariah - Jassical Mufidah; Muhammad Fahmul Iltiham; M. Mukhsinin Syu'abi (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to analyze the implementation of the Free Nutritious Meal Program (MBG) on the economy of beneficiary families and to review it from the perspective of Maqasid al-Shariah. A qualitative approach with a case study design was employed at the Nutrition Service Unit (SPPG) Lolawang, Mojokerto. Data were collected through observation, in-depth interviews, and documentation, then analyzed interactively through data reduction, presentation, and conclusion drawing. The findings reveal that the MBG program has been implemented in a fairly organized manner, although it still faces constraints such as limited aid quantities, suboptimal distribution, and unequal targeting. From an economic perspective, the program reduces household consumption expenditure, stabilizes family finances, and creates room for allocating income toward more productive needs. Within the Maqasid al-Shariah framework, the MBG program aligns with the preservation of life (ḥifż al-nafs), intellect (ḥifż al-‘aql), wealth (ḥifż al-māl), and progeny (ḥifż al-nasl). Although the dimension of religious protection remains implicit, the MBG program overall embodies high public benefit (maslahah) and corresponds with the objectives of Shariah in realizing societal well-being